Laughter and ideology: a critical discourse analysis of changing representations of rape in Norman Lear's sitcoms. Issue 1 (2nd January 2017) - Kypker, Nicole S.
ABSTRACT: This article explores changing representations of rape in the sitcoms of American producer Norman Lear. Tremendously successful in the 1970s, the numerous shows created by Lear's production companies addressed a wide range of then-controversial societal issues. He was explicitly committed to social justice, and his sitcoms were didactically left-wing. Representations of rape in these shows, however, were in some instances problematic and appeared to perpetuate reactionary, victim-blaming narratives. In order to disassemble the mixed ideological messages in these texts, a critical discourse analysis, as developed by Norman Fairclough (2010), is conducted of one relevant episode of the sitcom Maude (Lear, CBS 1972–1978). In line with the methodological approach detailed by Fairclough, the analysis identifies relevant contemporaneous social, political and cultural ideological currents. These, often contradictory, collective values are then utilised to contextualise the episode's discursive representations of rape. Furthermore, the episode is juxtaposed with both earlier and subsequent depictions of the issue in Lear's sitcoms. It emerges that the producer's varying portrayals of rape closely reflect developments in the then-concurrent radical-feminist movement; with that social movement's growing influence throughout the 1970s, media and legal discourses on sexual assault changed, a development that can be tracked through the increasingly more empathetic representations in Lear's shows.